KEMAMPUAN MENULIS BIOGRAFI MELALUI MEDIA PEMBELAJARAN VIDEO DOKUMENTER SISWA KELAS VIII SMP TAHUN AJARAN 2017/2018 - Nadia, Lia; Marshanda, Dea; Suhaniah, Acih; Hilaliyah, Tatu; Tanjung, Elma Fiana (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the influence of documentary video media on the writing abilities of eighth-grade students at SMP Al-Hikmah Medan during the academic year 2017-2018. The research was conducted at SMP Al-Hikmah Medan with a population of 59 students from two classes, all of whom were included in the research sample. Class VIII 2 was designated as the experimental group, while Class VIII 1 served as the control group. This research utilized an experimental method, a technique designed to reveal clear facts about the phenomena under investigation. The data collection tool employed was a written test. The writing abilities of biographies using documentary video media in the experimental class were deemed good, as 13 students (43.33%) fell within the 80-100 range, 13 students (43.33%) achieved a "very good" rating, 15 students (50%) attained a "good" rating, and 2 students (6.66%) received a "less satisfactory" rating. In contrast, the writing abilities of biographies without the use of documentary video media were less satisfactory, with 17 students (58.6%) falling within the 40-45 range. Based on the test results, it can be concluded that the learning outcomes of students recommended to use documentary video media were higher compared to those who did not use such media in their biography writing abilities in the eighth grade at SMP Al-Hikmah Medan during the academic year 2017-2018. This conclusion is supported by the results of hypothesis testing, where t-value > t-table, specifically 2.22 > 1.532, indicating that Ho (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. This means that there is an influence of using documentary video media as a learning model on the writing abilities of eighth-grade students at SMP Al-Hikmah Medan during the academic year 2017-2018.